Feeding Patterns Related to Nutritional Status in Stunted Toddlers - Retno Sari, Deni; Murwati, Murwati; Istikhomah, Henik (Jurnal Kebidanan dan Kesehatan Tradisional, 2024)
Background: Stunting can occur as a result of malnutrition, especially during the first 1000 days of life (HPK). Poor nutrition during pregnancy, growth, and early childhood can cause children to become stunted. The purpose of this study was to determine the relationship between feeding patterns and nutritional status in stunted toddlers at the North Klaten Community Health Center in Klaten Regency.  Methods: This study used an analytical observational design with a cross-sectional approach. The study population consisted of all mothers with stunted toddlers, totaling 234 people, using proportional stratified random sampling, resulting in a sample of 71 respondents. The research instruments used were the CFQ (Child Feeding Questionnaire) and anthropometric observation sheets. The validity and reliability of the instruments had been tested in previous studies. Data were analyzed univariately and bivariately using the chi-square test.  Results: The results showed that most feeding patterns were inappropriate (69%) and the nutritional status of stunted toddlers was classified as short (56.3%). The chi-square test obtained a p-value of 0.004 (p<0.05), which means that there is a significant relationship between feeding patterns and the nutritional status of stunted toddlers.  Conclusion: The study shows that the more appropriate the feeding patterns applied by mothers, the better the nutritional status of their children. Health workers need to improve education for mothers about the importance of feeding patterns appropriate for their children's age and involve nutritionists and posyandu cadres in monitoring toddler growth.